Effects of cholecalciferol supplementation on depressive symptoms, C-peptide, serotonin, and neurotrophin-3 in type 2 diabetes mellitus: A double-blind, randomized, placebo-controlled trial - Putranto, Rudi; Setiati, Siti; Nasrun, Martina W.; Witjaksono, Fiastuti; Immanuel, Suzanna; Subekti, Imam; Harimurti, Kuntjoro; Siswanto, Agus; Shatri, Hamzah; Suwarto, Suhendro; Megantara, Marcelino A. (Narra J, 2024)
The coexistence of depression and type 2 diabetes mellitus (T2DM) can significantly worsen disease prognosis and lower quality of life. Emerging evidence suggests that vitamin D deficiency contributes to the progression of T2DM and is closely associated with the development of depression. The aim of this study was to investigate the effects of cholecalciferol on depression in patients with T2DM, exploring its mechanisms by analyzing its impact on C-peptide, serotonin, and neurotrophin-3 levels. A double-blind, randomized, placebo-controlled clinical trial was conducted at Cipto Mangunkusumo General Hospital, Jakarta, Indonesia, from April 2021 to September 2022. Patients with T2DM and depressive symptoms were randomly assigned to two groups: received 4000 IU of cholecalciferol daily and received a placebo for 12 weeks. Depression was assessed using the Beck Depression Inventory-II (BDI-II) before and 12 weeks after the intervention. The levels of C-peptide, serotonin, and neurotrophin-3 were measured at the end of the fourth week of intervention using the enzyme-linked immunosorbent assay (ELISA) method. Between-group comparisons were made using independent Student t-tests and Mann-Whitney U tests. Paired Student t-tests or Wilcoxon tests were applied for within-group comparisons between pre- and post-intervention. A total of 70 T2DM patients with depression were included in this study, comprising 38 patients in the cholecalciferol group and 32 in the placebo group. C-peptide levels increased significantly in the cholecalciferol group compared to the placebo group (p=0.006). No significant differences were observed in serotonin and NT-3 levels between the cholecalciferol group compared to the placebo group. The cholecalciferol group had a significantly greater reduction in BDI-II scores compared to the placebo group (p<0.001). This trial highlights that taking cholecalciferol might help ease mild to moderate depression symptoms in patients with T2DM by enhancing c-peptide levels, though its effects on serotonin and neurotrophin-3 are still unclear.